Policy shocks, current account and the macroeconomy in a developing country: A Keynesian approach. Issue 3 (2nd August 2019) - Basu, Moumita; Nag, Ranjanendra Narayan
Abstract : Purpose: This is a theoretical paper in the field of international macroeconomics. The purpose of this paper is to focus on a dynamic interaction between current account imbalance and unemployment in response to some policy-induced shocks for a small open economy under a flexible exchange rate. Design/methodology/approach: The paper uses a two-sector framework: one sector is traded and another is the non-traded sector that is subject to an effective demand constraint. The current account imbalance arises due to the discrepancy between production of traded goods, household consumption of traded goods and government purchases of importables. The authors keep the asset structure simple by considering only domestic currency and foreign bonds that are imperfect substitutes. The paper considers a standard methodology of dynamic adjustment process involving change in foreign exchange reserves and exchange rate under perfect foresight. The saddle path properties of the equilibrium are also examined. Findings: The results of comparative static exercises depend on a set of structural features of a developing country, which include asset substitutability, wage price rigidity and sectoral asymmetries. The paper shows that expansionary monetary policy, balanced budget fiscal expansion and financial liberalization have an ambiguous effect on the current account balance, foreign exchange reserves, non-traded sector and the level of employment. Originality/value: The existence of Keynesian unemployment with fixed prices is the key ingredient of this paper. The paper introduces the problem of effective demand to analyze the dynamics of current account balance and exchange rate, which, in turn, determine the sectoral composition of output and level of employment.